India and the Knowledge Economy : Leveraging Strengths and Opportunities - Dahlman, Carl; Utz, Anuja (Washington, DC : World Bank, 2012)
In the global knowledge economy of the twenty-first century, India's development policy challenges will require it to use knowledge more effectively to raise the productivity of agriculture, industry, and services and reduce poverty. India has made tremendous strides in its economic and social development in the past two decades. Its impressive growth in recent years-8.2 percent in 2003-can be attributed to the far-reaching reforms embarked on in 1991 and to opening the economy to global competition. In addition, India can count on a number of strengths as it strives to transform itself into a knowledge-based economy-availability of skilled human capital, a democratic system, widespread use of English, macroeconomic stability, a dynamic private sector, institutions of a free market economy; a local market that is one of the largest in the world; a well-developed financial sector; and a broad and diversified science and technology infrastructure, and global niches in IT.